Characteristics of Yoga Practitioners, Motivators, and Yoga Techniques of Choice: A Cross-sectional Study - Telles, Shirley; Sharma, Sachin Kumar; Singh, Nilkamal; Balkrishna, Acharya (Frontiers in Public Health, 2017)
Abstract Background: The characteristics of yoga practitioners and factors motivating people to practice yoga have been studied in the United States and in Australia. The present study aimed to determine the characteristics of yoga users in India, the factors which motivate them to practice yoga, and the yoga techniques of choice. Materials and Methods: The study was a one-time, cross-sectional survey based on convenience sampling. Inclusion criteria were: (a) a minimum of 1 week experience of yoga and (b) at least 10 years of age. 14250 people received the survey. After excluding those who did not meet the inclusion criteria or filled in the survey incompletely/incorrectly, 5157 respondents were included in the study. Results: Out of 5157 respondents, there were more males (67.3%), aged between 21 to 44 years (33.7% of the sample surveyed), educated up to high school (62.5%), students (39.3%), and those who had between 1 to 12 months of experience in yoga (54.4%). The first most common reason to practice yoga for all respondents was physical fitness. Three of the remaining reasons to practice yoga differed significantly with age: (i) yoga for disease management (χ2 = 17.62, p < 0.005), (ii) yoga as a hobby (χ2 = 10.87, p < 0.05) and (iii) yoga based on the guru’s (teacher’s) instructions (χ2 = 20.05, p < 0.001). The yoga technique of choice [i.e., (i) asanas (χ2 = 23.17, p < 0.001), (ii) pranayama (χ2 = 19.87, p < 0.001) or (iii) meditation (χ2 = 9.64, p < 0.05)] differed significantly across age groups. Conclusions: In India a yoga practitioner was more likely to be male, between 21 and 44 years of age, high school educated, and a student. The reasons to practice yoga and the yoga technique of choice differed significantly with age.